Gamma and neutron attenuation characteristics of bricks containing zinc extraction residue as a novel shielding material - Gencel, Osman; Bozkurt, Ahmet; Kam, Erol; Yaras, Ali; Erdogmus, Ertugrul; Sutcu, Mucahit (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In recent years, people are exposed to radiation depending on the technology developed which may cause serious incurable health problems. To protect from radiation exposure, various radiation shielding materials are used in different areas. In this study, zinc extraction residue (ZER), which is released during zinc production containing various heavy metals, was evaluated in clay-based brick manufacturing. The fired bricks were characterized in terms of radiation shielding, bulk density and compressive strength. Clay brick with 50% ZER was fired at 1000 degrees C. Bulk density and compressive strength of fired brick were found as 2.16 g/cm(3) and 12.6 MPa, respectively. The addition of ZER increased the density while reducing the compressive strength. Radiation shielding potential for the samples were evaluated both experimentally (using an Am-Be neutron source and a Cs-137 gamma source) and simulation-wise using the Monte Carlo technique. For this purpose, mass attenuation coefficients of gammas and total absorption cross-section of neutrons were determined through measurements. Additionally, Monte Carlo simulations were carried out under similar irradiation conditions. The MCNP simulation results were checked against those produced from XCOM database for photons and Phy-X/P SD for neutrons. Inclusion of ZER was found to elevate shielding capabilities especially at low photon energies because of the lead content of ZER. In addition, neutron attenuation characteristics of ZER bricks were observed to be relatively lower than that of fired clay brick because of the heavier ingredients existing in ZER extracts.
Keywords: Metallurgical waste; Radiation protection; Experimental measurement; Monte Carlo simulation; Lead-based shielding materials; BORON WASTE; X-RAY; CONCRETE; GLASSES; LIGHTWEIGHT; COMPOSITES; STRENGTH; SLUDGE; BI2O3; Nuclear Science & Technology